Schizandrin Protects Primary Rat Cortical Cell Cultures from Glutamate-Induced Apoptosis by Inhibiting Activation of the MAPK Family and the Mitochondria Dependent Pathway - Wen-Huang Peng (Molecules, 2012)
Glutamate-induced excitotoxicity has been implicated in a variety of neuronal degenerative disorders. In the present study, we investigated the possible neuroprotective effects of schizandrin against apoptosis of primary cultured rat cortical cells induced by glutamate. Glutamate (10 μM) administered for 24 h decreased the expression of Bcl-2 and Bcl-XL protein, whereas increased the expression of Bax, Bak, apoptosis inducing factor (AIF), endonuclease G (Nodo G) and endoplasmic reticulum (ER) stress of caspase-12. Pretreatment with schizandrin (100 μM) before glutamate treatment increased the Bcl-XL and Bcl-2 expression and decreased Bax, Bak, AIF, Nodo G and caspase-12 compared with those only treated with glutamate. Furthermore, glutamate-induced phosphorylation of JNK, p38 and ERK mitogen-activated protein kinases (MAPK), and these effects were attenuated by schizandrin (100 μM) treatment. These results suggest that schizandrin possesses the neuroprotective effects. The molecular mechanisms of schizandrin against glutamate-induced apoptosis may involve the regulation of Bcl-2 family proteins expression, and ER stress through blocking the activation of JNK, ERK and p38 MAPK.